NILAI BUDAYA DAN KEARIFAN LOKAL MASYARAKAT KABUPATEN BATANGHARI DALAM CERITA TAPA MALENGGANG: SUATU KAJIAN SEMIOTIK - Oky Akbar; Maizar Karim; Warni Warni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims, (1) to find cultural values, (2) to find the form of local wisdom, (3) to find the meaning of the story based on signs. This research is descriptive-qualitative to reveal the whole meaning of the story. The data source is the story of Tapa Malenggang written by M. Rasyid who comes from Batanghari Regency. Collecting data using read-note and interview techniques. The story of Tapa Malenggang is read over and over again accompanied by notes of the findings. The data was strengthened by an open interview with M. Rasyid. The results of the study include the theme and message of the story, cultural values related to the relationship between humans and God, humans with nature, humans with society, humans with humans, and human relationships with oneself as well as local wisdom of the people of Batanghari Regency both in the form of abstracts and activities. The conclusion is that the Tapa Malenggang story is a romantic story that describes the life of the people of Batanghari Regency which is orderly and obedient to religion and customs and shows a society that has a high scientific civilization, is visionary and cares about the environment.